Alterations and Prediction of Functional Profiles of Gut Microbiota After Fecal Microbiota Transplantation for Iranian Recurrent Clostridioides difficile Infection with Underlying Inflammatory Bowel Disease: A Pilot Study - Azimirad M; Jo Y; Kim MS; Jeong M; Shahrokh S; Aghdaei HA; Zali MR; Lee S; Yadegar A; Shin JH (Dove Medical Press, 2022)
Masoumeh Azimirad,1,* YoungJae Jo,2,* Min-Sueng Kim,2 Minsoo Jeong,2 Shabnam Shahrokh,3 Hamid Asadzadeh Aghdaei,4 Mohammad Reza Zali,3 Seungjun Lee,5 Abbas Yadegar,1 Jae-Ho Shin2 1Foodborne and Waterborne Diseases Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 2Department of Applied Biosciences, Kyungpook National University, Daegu, 41566, Republic of Korea; 3Gastroenterology and Liver Diseases Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 4Basic and Molecular Epidemiology of Gastrointestinal Disorders Research Center, Research Institute for Gastroenterology and Liver Diseases, Shahid Beheshti University of Medical Sciences, Tehran, Iran; 5Department of Food Science and Nutrition, College of Fisheries Science, Pukyong National University, Busan, Republic of Korea*These authors contributed equally to this workCorrespondence: Abbas Yadegar; Jae-Ho Shin Tel +98-21-22432518; +82 53-950-5716Fax +98-21-22432527; +82 53-953-7233Email babak_y1983@yahoo.com; jhshin@knu.ac.krBackground and Purpose: Fecal microbiota transplantation (FMT) has emerged for the therapeutic treatment of recurrent Clostridioides difficile infection (rCDI) with concurrent inflammatory bowel disease (IBD). As the first Iranian population cohort, we examined how gut microbiota and their functional profiles change in Iranian rCDI patients with underlying IBD before and after FMT.Patients and Methods: FMT was performed to eight IBD patients via colonoscopy. Profiles of gut microbiota from donors and recipients were investigated using 16S rRNA gene sequence analysis.Results: Patients experienced no IBD flare-ups or other adverse effects, and all recovered to full health. Moreover, all rCDI patients lacked the Bacteroidetes present in donor samples. After FMT, the proportion of Bacteroidetes increased until a normal range was achieved. More specifically, the relative abundance of Prevotella was found to increase significantly following FMT. Prevotella was also found to correlate negatively with inflammation metrics, suggesting that Prevotella may be a key factor for resolving CDI and IBD. Gut microbiota diversity was found to increase following FMT, while dysbiosis decreased. However, the similarity of microbial communities of host and recipients did not increase, and wide variation in the extent of donor stool engraftment indicated that the gut bacterial communities of recipients do not shift towards those of donors.Conclusion: FMT leads to significant alterations of the community structure of gut bacteria in rCDI patients with IBD. The change in relative abundance of Proteobacteria and bacterial diversity indicated that FMT promotes recovery from intestinal permeability and inflammation in rCDI patients. Moreover, strong negative correlation between Prevotella and inflammation index, and decreased dysbiosis index advocate that the improvement of CDI is possibly due to gut microbiome alteration. Collectively, our findings show that FMT would be a promising therapy to help reprogram the gut microbiome of Iranian rCDI patients with IBD.Keywords: fecal microbiota transplantation, Clostridioides difficile infection, inflammatory bowel disease, gut microbiome, functional profiles, gut dysbiosis